The Constitution is A Legal Guarantee For The Development of The Country and The Well-Being of Society - Madumarov Talantbek Tolibjonovich; G’ulomjonov Odiljon Raximjon o’g’li (Research Parks Publishers, 2021)
Constitutions have a law and an internal structure. The external structure of the Constitution describes its relationship with other sources of law, the totality of relations, its place and role in the legal system and its significance in the system of social and normative regulation in society